Disturbed Placental Imprinting in Preeclampsia Leads to Altered Expression of DLX5, a Human-Specific Early Trophoblast Marker. Issue 19 (7th November 2017) - Zadora, Julianna; Singh, Manvendra; Herse, Florian; Przybyl, Lukasz; Haase, Nadine; Golic, Michaela; Yung, Hong Wa; Huppertz, Berthold; Cartwright, Judith E.; Whitley, Guy; Johnsen, Guro M.; Levi, Giovanni; et al.
Abstract : Background: Preeclampsia is a complex and common human-specific pregnancy syndrome associated with placental pathology. The human specificity provides both intellectual and methodological challenges, lacking a robust model system. Given the role of imprinted genes in human placentation and the vulnerability of imprinted genes to loss of imprinting changes, there has been extensive speculation, but no robust evidence, that imprinted genes are involved in preeclampsia. Our study aims to investigate whether disturbed imprinting contributes to preeclampsia. Methods: We first aimed to confirm that preeclampsia is a disease of the placenta by generating and analyzing genome-wide molecular data on well-characterized patient material. We performed high-throughput transcriptome analyses of multiple placenta samples from healthy controls and patients with preeclampsia. Next, we identified differentially expressed genes in preeclamptic placentas and intersected them with the list of human imprinted genes. We used bioinformatics/statistical analyses to confirm association between imprinting and preeclampsia and to predict biological processes affected in preeclampsia. Validation included epigenetic and cellular assays. In terms of human specificity, we established an in vitro invasion-differentiation trophoblast model. Our comparative phylogenetic analysis involved single-cell transcriptome data of human, macaque, and mouse preimplantation embryogenesis. Results: We found disturbed placental imprinting in preeclampsia and revealed potential candidates, including GATA3 and DLX5, with poorly explored imprinted status and no prior association with preeclampsia. As a result of loss of imprinting, DLX5 was upregulated in 69% of preeclamptic placentas. Levels of DLX5 correlated with classic preeclampsia markers. DLX5 is expressed in human but not in murine trophoblast. The DLX5 high phenotype resulted in reduced proliferation, increased metabolism, and endoplasmic reticulum stress-response activation in trophoblasts in vitro. The transcriptional profile of such cells mimics the transcriptome of preeclamptic placentas. Pan-mammalian comparative analysis identified DLX5 as part of the human-specific regulatory network of trophoblast differentiation. Conclusions: Our analysis provides evidence of a true association among disturbed imprinting, gene expression, and preeclampsia. As a result of disturbed imprinting, the upregulated DLX5 affects trophoblast proliferation. Our in vitro model might fill a vital niche in preeclampsia research. Human-specific regulatory circuitry of DLX5 might help explain certain aspects of preeclampsia. Abstract : Supplemental Digital Content is available in the text.